Training on Making Sweet Potato Balls for PKK Women in Watesnegoro Village: Pelatihan Pembuatan Cemilan Bola – Bola Ubi kepada Ibu-Ibu Pkk Desa Watesnegoro - Zarkasi, Muhammad Afandi; Zahroh, Fatimatuz; Chusna, Asma’ul; Prapanca, Detak (Procedia of Social Sciences and Humanities, 2022)
At the end of 2021, the Indonesian economy began to stabilize because the Covid 19 pandemic had begun to decline. All activities such as school can be carried out offline or face to face. In addition, organizations in the village have also begun to actively regroup as before, one of which is the PKK organization in the village of Watesnegoro. Most of the PKK women in this village rely on income from their husbands' wages. Meanwhile, as housewives at this time, they are required to be creative and smart to adapt in the present. Based on these problems as a form of student responsibility in carrying out Real Work Lectures, namely by doing community service in the form of holding training on making sweet potato balls snack creations. Implementation time of activities with a period of 5 days. After the training, this community service activity is expected to increase the knowledge and skills of PKK mothers. The result of this community service is that PKK women are able to carry out and increase the role of the group of housewives through innovation in the use of sweet potato raw materials into processed sweet potato balls in order to maintain food security and improve the household economy. So it is hoped that from a small scope, namely the family, it will have a big impact on the surrounding community. This is because the role of a mother is very important in the family. In addition, PKK women are able to make sweet potato balls to meet their own needs even as a business opportunity.